New cell sources for CAR-based immunotherapy - Marzieh Mazinani; Fatemeh Rahbarizadeh (Biomarker Research, 2023)
Abstract Chimeric antigen receptor (CAR) T cell therapy, in which a patient’s own T lymphocytes are engineered to recognize and kill cancer cells, has achieved striking success in some hematological malignancies in preclinical and clinical trials, resulting in six FDA-approved CAR-T products currently available in the market. Despite impressive clinical outcomes, concerns about treatment failure associated with low efficacy or high cytotoxicity of CAR-T cells remain. While the main focus has been on improving CAR-T cells, exploring alternative cellular sources for CAR generation has garnered growing interest. In the current review, we comprehensively evaluated other cell sources rather than conventional T cells for CAR generation.